Polygamy in Family Law: Gender Perspectives and Its Implications for Women's Rights - Supriadi; Janur, Nur Akifah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to analyze in depth how the practice of polygamy in Majene Regency affects the fulfillment and protection of women's rights in the context of family law. This research is a descriptive qualitative research in understanding the practice of polygamy in Majene Regency and its impact on the fulfillment and protection of women's rights. Primary data, namely data obtained directly from four informants, namely (a) Wife in polygamous marriage, (b) Daughter from polygamous marriage, (c) One of the Women's Institutions in Majene Regency, (d) Religious Leaders in Majene Regency. Meanwhile, secondary data comes from documents or literature related to the object of research. Data collection techniques include interviews, observations and documentation studies. Data analysis was carried out thematically through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the practice of polygamy in Majene Regency has a significant impact on the fulfillment and protection of women's rights, especially first wives, in the context of family law. Although there are clear legal rules, their implementation is still constrained by low legal awareness, weak supervision, and a strong patriarchal culture that places women in subordinate positions. In addition, children from polygamous families also experience emotional impacts due to the inequality of parental attention, which has so far received less attention in legal policies. Therefore, a more holistic and gender-perspective legal approach is needed that not only focuses on formal aspects, but also considers social, cultural, and psychological factors to realize fair and comprehensive legal protection for all family members.